Transcripts of internal messages from British military forces and the Royal Irish Constabulary, - Irish Volunteers. Cork Brigade (1921)
Includes related correspondence between I.R.A. Southern Division Intelligence Officers, some manuscript notes and annotations and general intelligence information.